OVA-PEG-R848 nanocapsules stimulate neonatal conventional and plasmacytoid dendritic cells - Sebastian Wirsching; Marina Machtakova; Frauke Borgans; Frauke Borgans; Leah Pretsch; Michael Fichter; Michael Fichter; Michael Fichter; Maximiliano L. Cacicedo; Héloïse Thérien-Aubin; Héloïse Thérien-Aubin; Katharina Landfester; et al. (Frontiers in Pediatrics, 2022)
Childhood mortality represents a major issue with 5. 3 million worldwide deaths of children under 5 years of age in 2019. Approximately half of those deaths can be attributed to easily preventable, infectious diseases. Currently approved neonatal vaccines are typically effective only after multiple doses leaving infants especially vulnerable during the first 6 months of life. Survival rates could be improved significantly by developing new and more potent vaccines that are capable of overcoming inherently tolerogenic neonatal immune systems. TLR agonists have garnered a great deal of attention in recent years due to their extensive capacities to activate innate immunity. Herein, the superior capacity of the TLR7/8 agonist, resiquimod (R848), to activate adult and neonatal primary peripheral blood dendritic cells is demonstrated. Moreover, R848 can be conjugated to polyethylene glycol and encapsulated in ovalbumin nanocapsules to efficiently co-deliver antigen and adjuvant in vitro. This study is among the first to demonstrate the capacity of encapsulated R848 to activate neonatal dendritic cells. These findings support the potential incorporation of R848 as adjuvant in neonatal vaccines, making them more effective in eliciting a robust immune response.